1993
DOI: 10.1063/1.465958
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the β–γ phase transition in single crystal malononitrile by polarized Raman spectroscopy

Abstract: Temperature dependent, polarized Raman spectra in the lattice mode region for sublimed, single crystal malononitrile through the D-r phase transition (T,=294.7 K) are reported. Symmetry assignments and frequencies of vibrational modes are made and compared to previous studies. Nine out of 12 possible lattice modes are observed in each phase with three of the observed modes being affected by the phase transition. The temperature dependence of these three affected modes is attributed to cyano group and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The change in crystal symmetry from P2 1 /n to P 1 space groups occurs by a distortion of the α or γ -phase that can be described by the irreducible representation B g at zero wavevector. Whilst the study of Le Calvé et al [13] did not determine the symmetry of the soft mode, the only symmetries of the Raman-active modes are A g and B g , and a subsequent study by Bonafede and Eckhardt [18] accounted for all A g modes. This implies that the soft mode has symmetry B g , independently confirming the change in space group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in crystal symmetry from P2 1 /n to P 1 space groups occurs by a distortion of the α or γ -phase that can be described by the irreducible representation B g at zero wavevector. Whilst the study of Le Calvé et al [13] did not determine the symmetry of the soft mode, the only symmetries of the Raman-active modes are A g and B g , and a subsequent study by Bonafede and Eckhardt [18] accounted for all A g modes. This implies that the soft mode has symmetry B g , independently confirming the change in space group.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the phase transitions in malononitrile have been based on spectroscopic methods [11][12][13][14][15][16][17][18]. Of particular note are the studies of Le Calvé et al [13] and Krauzman et al [14], who identified the soft mode responsible for the two displacive phase transitions.…”
Section: Introductionmentioning
confidence: 99%